ULOGA ODNOSA S JAVNOŠĆU I KANALA INFORMIRANJA U PROMOVIRANJU OS BIH U SVRHU ZAPOŠLJAVANJA MLADIH - Sivrić, Ivana; Kukić, Damir; Jerkić, Ivica (Hum, 2024)
Development of the Internet and information and communication technologies in the modern context should enable young users to effectively connect and receive information through various communication channels in order to better interact with future employers. One of the most important channels of communication for young people in the online space is undoubtedly social networks, through which young people can both inform themselves and communicate. Social networks especially contribute to socialization and connecting users in virtual communities, where they exchange experiences and information that can be socially useful, even for finding future desirable employers. This is also confirmed by a public opinion survey from 2022 on the attitudes of young people and parents towards employment and retention in the Armed Forces of Bosnia and Herzegovina, which were analyzed for the purposes of this paper with a special focus on information channels. Information channels through which young people get (relevant) information are a very important item in the perception, identification and affirmation of the military profession with the aim of obtaining quality human resources. In addition to the working conditions mentioned by the respondents as key elements for employment in the Armed Forces of Bosnia and Herzegovina, it is necessary to effectively improve the media promotion and perception of the Armed Forces of Bosnia and Herzegovina in the public, which is particularly pointed out and stated in the set of recommendations listed in the concluding part of this paper.